Semiconductor Nanoparticle Composites

A semiconductor nanoparticle composite with aliphatic and polar ligands addresses the issue of ligand detachment and oxidation, ensuring high fluorescence efficiency and dispersibility in polar solvents, suitable for applications in displays and solar cells.

JP7616535B2Active Publication Date: 2025-01-17SHOEI CHEM IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021521906
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-31
Filing Date
2020-05-29
Publication Date
2025-01-17
Estimated Expiration
2040-05-29

AI Technical Summary

Technical Problem

Semiconductor nanoparticles face challenges in maintaining fluorescence quantum efficiency and dispersibility in polar solvents due to ligand detachment at high temperatures, especially during processes involving oxygen and high temperatures, leading to oxidation of the nanoparticle surface.

Method used

A semiconductor nanoparticle composite is developed with a combination of aliphatic and polar ligands coordinated on the nanoparticle surface, where the aliphatic ligand has an aliphatic hydrocarbon group and the polar ligand includes a hydrophilic functional group, with a specific mass ratio and desorption temperature profile to maintain stability and dispersibility.

Benefits of technology

The composite achieves high fluorescence quantum efficiency and dispersibility in polar solvents, with improved heat resistance and reduced ligand detachment, enabling effective application in various fields including displays and solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616535000003
    Figure 0007616535000003
  • Figure 0007616535000004
    Figure 0007616535000004
  • Figure 0007616535000005
    Figure 0007616535000005
Patent Text Reader

Abstract

The present invention provides a semiconductor nanoparticle composite material which can be dispersed in a polar dispersion medium and has a high ligand elimination temperature. A semiconductor nanoparticle composite material according to one embodiment is a semiconductor nanoparticle composite material in which two or more types of ligand, including an aliphatic ligand and a polar ligand, are coordinated at the surface of a semiconductor nanoparticle. The ligands comprise an organic group and a coordinating group. The aliphatic ligand is a ligand in which the organic group is an aliphatic hydrocarbon group. The polar ligand contains a hydrophilic functional group in the organic group. The mass ratio of the aliphatic ligand and the polar ligand (aliphatic ligand / polar ligand) is 0.05-1.00. The ratio ({(XH) / L}×100) of the mass-loss rate (XH) of the semiconductor nanoparticle composite material within the temperature range 350-550°C in thermogravimetric analysis relative to the mass percentage (L) of all ligands relative to the semiconductor nanoparticle composite material at room temperature is 10-55.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to semiconductor nanoparticle composites. This application claims priority to Japanese Patent Application No. 2019-103247, filed on May 31, 2019, and incorporates by reference all of the contents of said Japanese Patent Application. [Background technology]

[0002] Semiconductor nanoparticles that are small enough to exhibit the quantum confinement effect have a band gap that depends on the particle size. Excitons formed in the semiconductor nanoparticles by means of photoexcitation, charge injection, etc. recombine to emit photons with energy corresponding to the band gap, so that light emission at a desired wavelength can be obtained by appropriately selecting the composition of the semiconductor nanoparticles and their particle size.

[0003] In the early stages of research into semiconductor nanoparticles, the focus was on elements containing Cd and Pb. However, because Cd and Pb are regulated substances under the Restriction of the Use of Certain Hazardous Substances, research has been focused in recent years on non-Cd- and non-Pb-based semiconductor nanoparticles.

[0004] Attempts have been made to apply semiconductor nanoparticles to various applications, such as displays, biological labeling, and solar cells. In particular, for display applications, semiconductor nanoparticles have begun to be made into films and used as wavelength conversion layers. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2015 / 156226 [Patent Document 2] JP 2013-136498 A [Non-patent literature]

[0006] [Non-Patent Document 1] Takashi Jin, "Semiconductor Quantum Dots, Their Synthesis and Applications to Life Sciences," Production and Technology, Vol. 63, No. 2, pp. 58-63, 2011 [Non-Patent Document 2] Fabien Dubois et al, “A Versatile Strategy for Quantum Dot Ligand Exchange” J.AM.CHEM.SOC Vol.129, No.3, p.482-483, 2007 [Non-Patent Document 3] Boon-Kin Pong et al, “Modified Ligand-Exchange for Efficient Solubilization of CdSe / ZnS Quantum Dots in Water: A Procedure Guided by Computational Studies” Langmuir Vol.24, No.10, p.5270-5276, 2008 [Non-Patent Document 4] Samsulida Abd. Rahman et al, “Thiolate-Capped CdSe / ZnS Core-Shell Quantum Dots for the Sensitive Detection of Glucose” Sensors Vol.17, No.7, p.1537, 2017 [Non-Patent Document 5] Whitney Nowak Wenger et al, “Functionalization of Cadmium Selenide Quantum Dots with Poly(ethylene glycol): Ligand Exchange, Surface Coverage, and Dispersion Stability” Langmuir, Vol.33, No.33, pp8239-8245, 2017 [Non-Patent Document 6] Jagdeep Singh et al., “Encapsulation of Zinc Oxide Nanorods and Nanoparticles” Langmuir, vol.25, No.17, pp9947-9953, 2009 Summary of the Invention [Problem to be solved by the invention]

[0007] Semiconductor nanoparticles and semiconductor nanoparticle composites are generally dispersed in a dispersion medium to prepare a dispersion liquid and applied in various fields. In particular, to be practical, it is necessary to disperse them in a dispersion medium.

[0008] Furthermore, depending on the application, semiconductor nanoparticles and semiconductor nanoparticle composites may be exposed to high temperatures of about 200°C in the presence of oxygen during processes such as the filming process of semiconductor nanoparticles, the baking process of semiconductor nanoparticle-containing photoresist, or the solvent removal and resin curing process after inkjet patterning of semiconductor nanoparticles. In this case, ligands that have a weak binding strength with the semiconductor nanoparticles are more likely to detach from the surface of the semiconductor nanoparticles at lower temperatures. When ligands detach from the surface of the semiconductor nanoparticles, the surface of the semiconductor nanoparticles is oxidized, leading to a decrease in the fluorescence quantum efficiency.

[0009] Patent Document 1 discloses the desorption of ligands from semiconductor nanoparticle composites that can be dispersed in non-polar solvents. Ligand desorption is within 70% when the temperature is raised from 350°C to 490°C. However, the semiconductor nanoparticle composite described in Patent Document 1 can be dispersed in non-polar solvents, but not in polar solvents. When dispersing in a polar solvent, it is necessary to change the ligand coordinated to the semiconductor nanoparticles to make the semiconductor nanoparticle composite dispersible in a polar solvent. Furthermore, the ligand of the semiconductor nanoparticle composite that disperses in a polar solvent must have a high desorption temperature.

[0010] Non-Patent Documents 1 to 5 and Patent Document 2 disclose that the dispersion medium in which the semiconductor nanoparticles can be dispersed can be changed by exchanging the ligands coordinated to the surface of the semiconductor nanoparticles with different ligands. However, although these semiconductor nanoparticle conjugates can be dispersed in polar solvents, there is a problem in that the fluorescence quantum efficiency of the semiconductor nanoparticle conjugate is reduced by the ligand exchange.

[0011] Accordingly, an object of the present invention is to provide a semiconductor nanoparticle conjugate that is dispersible in a polar dispersion medium and has a high ligand desorption temperature. [Means for solving the problem]

[0012] The semiconductor nanoparticle composite according to an embodiment of the present invention comprises: A semiconductor nanoparticle composite in which two or more types of ligands, including an aliphatic ligand and a polar ligand, are coordinated to the surface of a semiconductor nanoparticle, The ligand comprises an organic group and a coordinating group, The aliphatic ligand has an aliphatic hydrocarbon group as the organic group. The polar ligand comprises a hydrophilic functional group on the organic group, the mass ratio of the aliphatic ligand to the polar ligand (aliphatic ligand / polar ligand) is 0.05 to 1.00; The mass loss rate (X) of the semiconductor nanoparticle composite at room temperature in the range of 350°C to 550°C in thermogravimetric analysis is H ) percentage ({(X H ) / L}×100) is 10 or more and 55 or less, A semiconductor nanoparticle composite. In addition, a semiconductor nanoparticle composite according to another embodiment of the present invention is A semiconductor nanoparticle composite in which two or more types of ligands, including an aliphatic ligand and a polar ligand, are coordinated to the surface of a semiconductor nanoparticle, The ligand comprises an organic group and a coordinating group, The aliphatic ligand has an aliphatic hydrocarbon group as the organic group. The polar ligand comprises a hydrophilic functional group on the organic group, the mass ratio of the aliphatic ligand to the polar ligand (aliphatic ligand / polar ligand) is 0.05 to 1.00; The mass loss rate (X H ) is 2% or more and 15% or less, A semiconductor nanoparticle composite. In this application, the range indicated by "~" is the range including the numbers on both ends. In addition, in this application, "room temperature" refers to 25°C. Effect of the Invention

[0013] According to the above invention, it is possible to provide a semiconductor nanoparticle composite that is dispersible in a polar dispersion medium and has a high ligand desorption temperature. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 shows the results of thermogravimetric analysis of a semiconductor nanoparticle composite according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing infrared absorption spectra of the semiconductor nanoparticle conjugate according to the embodiment of the present invention and the ligand alone. [Diagram 3] FIG. 3 is a graph obtained by fitting the measured and calculated infrared absorption spectrum of the semiconductor nanoparticle composite according to an embodiment of the present invention. [Figure 4] FIG. 4 is a diagram showing the configuration of the infrared absorption spectrum of each ligand component in a fitting curve for the absorption peak of CH stretching of a semiconductor nanoparticle composite according to an embodiment of the present invention. [Diagram 5] FIG. 5 is a diagram showing infrared absorption spectra before and after heat treatment of the semiconductor nanoparticle composite according to an embodiment of the present invention. [Figure 6] FIG. 6 shows the results of thermogravimetric analysis of the semiconductor nanoparticle composite of Example 10. [Figure 7]FIG. 7 shows the results of thermogravimetric analysis of the semiconductor nanoparticle composite of Example 16. [Figure 8] FIG. 8 shows the results of thermogravimetric analysis of the semiconductor nanoparticle composite of Example 17. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention relates to semiconductor nanoparticle composites. <Semiconductor nanoparticles> In the present invention, the semiconductor nanoparticle composite is a semiconductor nanoparticle composite having light emitting properties. The semiconductor nanoparticle composite of the present invention is a particle that absorbs light of 340 nm to 480 nm and emits light with an emission peak wavelength of 400 nm to 750 nm.

[0016] The full width at half maximum (FWHM) of the emission spectrum of the semiconductor nanoparticle composite is preferably 40 nm or less, and more preferably 38 nm or less. When the full width at half maximum of the emission spectrum is in the above range, color mixing can be reduced when the semiconductor nanoparticle composite is applied to a display or the like.

[0017] The fluorescence quantum efficiency (QY) of the semiconductor nanoparticle composite is preferably 80% or more, more preferably 85% or more. When the fluorescence quantum efficiency of the semiconductor nanoparticle composite is 80% or more, color conversion can be performed more efficiently. In the present invention, the fluorescence quantum efficiency of the semiconductor nanoparticle composite can be measured using a quantum efficiency measurement system.

[0018] -Semiconductor nanoparticles- The semiconductor nanoparticles constituting the semiconductor nanoparticle composite are not particularly limited as long as they satisfy the above-mentioned luminescence properties such as the fluorescence quantum efficiency and half-width, and may be particles made of one type of semiconductor or particles made of two or more different types of semiconductors. In the case of particles made of two or more different types of semiconductors, the semiconductors may form a core-shell structure. The type of semiconductor is not particularly limited, but examples thereof include InP, GaP, CdSe, CdS, ZnS, ZnSe, and ZnS. In particular, non-Cd-based semiconductors are preferable. Here, the semiconductor nanoparticles may contain compositions other than semiconductors as long as the properties of the semiconductor nanoparticles are not impaired.

[0019] In the case of particles containing two or more different semiconductors, the particles may be a mixture of the above-mentioned semiconductors. In the case of a core-shell structure, the particles may be core-shell type particles having a core containing a group III element and a group V element and a shell containing a group II element and a group VI element that covers at least a part of the core. Here, the shell may have a plurality of shells made of different compositions, and may have one or more gradient shells in which the ratio of the elements constituting the shell changes within the shell.

[0020] Specific examples of Group III elements include In, Al, and Ga. Specific examples of Group V elements include P, N and As. The composition for forming the core is not particularly limited, but from the viewpoint of light emission characteristics, InP is preferable.

[0021] The Group II element is not particularly limited, but examples thereof include Zn and Mg. Group VI elements include, for example, S, Se, Te, and O. The composition forming the shell is not particularly limited, but from the viewpoint of the quantum confinement effect, ZnS, ZnSe, ZnSeS, ZnTeS, ZnTeSe, etc. are preferable. In particular, when Zn element is present on the surface of the semiconductor nanoparticle, the effect of the present invention can be more effectively exhibited.

[0022] In the case where there are multiple shells, it is sufficient that at least one shell of the above-mentioned composition is included. In addition, in the case where there is a gradient type shell in which the ratio of the elements constituting the shell changes within the shell, the shell does not necessarily have to have the composition as indicated in the composition notation. Here, in the present invention, whether the shell covers at least a portion of the core and the element distribution inside the shell can be confirmed, for example, by composition analysis using energy dispersive X-ray spectroscopy with a transmission electron microscope (TEM-EDX).

[0023] <Method of producing semiconductor nanoparticles> An example of a method for producing semiconductor nanoparticles contained in a semiconductor nanoparticle composite will be disclosed below. (core) The cores of the semiconductor nanoparticles can be formed by mixing a Group III precursor, a Group V precursor, and, if necessary, an additive in a solvent and heating the resulting precursor mixture. Coordinating and non-coordinating solvents are used, including 1-octadecene, hexadecane, squalane, oleylamine, trioctylphosphine, and trioctylphosphine oxide. Group III precursors include, but are not limited to, acetates, carboxylates, and halides containing the Group III elements. The precursor of group V includes, but is not limited to, an organic compound or gas containing the group V element. When the precursor is a gas, the core can be formed by injecting the gas into a precursor mixture containing other gases and reacting them.

[0024] The semiconductor nanoparticles may contain one or more elements other than Group III and Group V elements as long as the effects of the present invention are not impaired. In this case, a precursor of the element may be added during the formation of the core. Examples of additives include dispersants such as carboxylic acids, amines, thiols, phosphines, phosphine oxides, phosphinic acids, and phosphonic acids, but are not limited thereto. The dispersant can also serve as a solvent. After the core of the semiconductor nanoparticle is formed, a halide can be added as necessary to improve the light emitting properties of the semiconductor nanoparticle.

[0025] In one embodiment, a metal precursor solution in which an In precursor and, if necessary, a dispersant are added to a solvent is mixed under vacuum, and the mixture is heated at 100°C to 300°C for 6 to 24 hours, after which a P precursor is added and the mixture is heated at 200°C to 400°C for 3 to 60 minutes and then cooled. A halogen precursor is further added and the mixture is heated at 25°C to 300°C, preferably 100°C to 300°C, more preferably 150°C to 280°C, to obtain a core particle dispersion liquid containing core particles.

[0026] (shell) By adding a shell-forming precursor to the synthesized core particle dispersion, the semiconductor nanoparticles can adopt a core-shell structure, thereby improving the fluorescence quantum efficiency (QY) and stability. The elements that make up the shell are thought to form an alloy, heterostructure, or amorphous structure on the surface of the core particle, but it is also possible that some of them migrate to the inside of the core particle by diffusion.

[0027] The added shell-forming element is mainly present near the surface of the core particle and plays a role in protecting the semiconductor nanoparticle from external factors. In the core-shell structure of the semiconductor nanoparticle, the shell preferably covers at least a part of the core, and more preferably uniformly covers the entire surface of the core particle.

[0028] In one embodiment, a Zn precursor and a Se precursor are added to the aforementioned core particle dispersion liquid, and then the mixture is heated at 150° C. to 300° C., preferably 180° C. to 250° C., and then a Zn precursor and a S precursor are added, and the mixture is heated at 200° C. to 400° C., preferably 250° C. to 350° C. This allows core-shell type semiconductor nanoparticles to be obtained. Here, although not particularly limited, examples of Zn precursors that can be used include carboxylates such as zinc acetate, zinc propionate, and zinc myristate, halides such as zinc chloride and zinc bromide, and organic salts such as diethylzinc. As the Se precursor, phosphine selenides such as tributylphosphine selenide, trioctylphosphine selenide, and tris(trimethylsilyl)phosphine selenide, selenols such as benzeneselenol and selenocysteine, and selenium / octadecene solutions can be used. As the S precursor, phosphine sulfides such as tributylphosphine sulfide, trioctylphosphine sulfide, and tris(trimethylsilyl)phosphine sulfide, thiols such as octanethiol, dodecanethiol, and octadecanethiol, and sulfur / octadecene solution can be used. The shell precursors may be mixed in advance and added all at once or in multiple portions, or each may be added separately all at once or in multiple portions. When the shell precursors are added in multiple portions, each addition may be heated at a different temperature.

[0029] In the present invention, the method for producing semiconductor nanoparticles is not particularly limited, and in addition to the methods described above, any method may be adopted, including conventional production methods such as the hot injection method, the homogeneous solvent method, the reverse micelle method, and the CVD method.

[0030] <Semiconductor nanoparticle composite> In the present invention, the semiconductor nanoparticle composite is a semiconductor nanoparticle having a ligand coordinated to the surface thereof. The term "coordination" used herein means that the ligand chemically affects the surface of the semiconductor nanoparticle. The ligand may be bonded to the surface of the semiconductor nanoparticle by a coordinate bond or any other bonding mode (e.g., a covalent bond, an ionic bond, a hydrogen bond, etc.), or may not necessarily be bonded when at least a portion of the surface of the semiconductor nanoparticle has a ligand.

[0031] (Ligand composition) In the present invention, the ligand coordinated to the semiconductor nanoparticle comprises an organic group and a coordinating group. The ligand in the semiconductor nanoparticle composite of the present invention includes an aliphatic ligand in which the organic group is an aliphatic hydrocarbon group, and a polar ligand in which the organic group contains a hydrophilic functional group. The aliphatic ligand preferably has one coordinating group and at least one aliphatic hydrocarbon group bonded thereto, and by adopting such a structure, the semiconductor nanoparticle composite can obtain a higher fluorescence quantum efficiency. The coordinating group of the aliphatic ligand is preferably selected from the group consisting of an amino group, a carboxyl group, a mercapto group, a phosphine group, and a phosphine oxide group. By adopting such a structure, a higher fluorescent quantum efficiency can be obtained.

[0032] The polar ligand has a hydrophilic functional group in the organic group. The organic group of the polar ligand preferably has at least one of a hydroxyl group, a carboxyl group, a carbonyl group, a mercapto group, an amino group, an ether bond, an ester bond, and a siloxane bond as a hydrophilic functional group. By having a hydrophilic functional group in the organic group of the polar ligand, dispersion in a polar dispersion medium becomes possible. In particular, when the coordinating group of the polar ligand is a mercapto group, the polar ligand can be strongly coordinated to the semiconductor nanoparticles, resulting in high fluorescence quantum efficiency and improved heat resistance of the semiconductor nanoparticle composite.

[0033] The molecular weight of the polar ligand is preferably 50 or more and 600 or less, more preferably 50 or more and 450 or less. By using a ligand having a molecular weight of 600 or less, the size and volume of the semiconductor nanoparticle composite are prevented from increasing, and when the semiconductor nanoparticle composite is applied to a dispersion liquid, a composition, a cured film, etc., it becomes easy to increase the mass fraction of the semiconductor nanoparticle composite relative to these. On the other hand, when the molecular weight is 50 or more, the effect of steric hindrance is fully exerted, and the occurrence of aggregation, etc. can be suppressed when the semiconductor nanoparticle composite is dispersed in a dispersion medium.

[0034] (Ligand ratio) The mass ratio of the aliphatic ligand to the polar ligand (aliphatic ligand / polar ligand) is preferably 0.05 to 1.00, more preferably 0.10 to 1.00, and even more preferably 0.20 to 0.80. When the mass ratio is within this range, the semiconductor nanoparticle composite can be dispersed in a dispersion medium with a high SP value, and a semiconductor nanoparticle composite with high heat resistance can be obtained.

[0035] (Ligand / Semiconductor Nanoparticles) The mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is preferably 0.1 to 0.7. When the mass ratio of the ligand to the semiconductor nanoparticles is within this range, the size and volume of the semiconductor nanoparticle composite are prevented from increasing, and when the semiconductor nanoparticle composite is applied to a dispersion liquid, a composition, a cured film, or the like, the mass fraction of the semiconductor nanoparticle composite relative to these can be increased. The mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is more preferably 0.1 to 0.5.

[0036] <Method of Manufacturing Semiconductor Nanoparticle Composite> An example of a method for producing a semiconductor nanoparticle composite will be disclosed below. There is no limitation on the method of coordinating the ligand to the semiconductor nanoparticles, but a ligand exchange method utilizing the coordination power of the ligand can be used. Specifically, the semiconductor nanoparticles in which the organic compound used in the process of producing the semiconductor nanoparticles is coordinated to the surface of the semiconductor nanoparticles are contacted with the target ligand in a liquid phase to obtain a semiconductor nanoparticle composite in which the target ligand is coordinated to the surface of the semiconductor nanoparticles. In this case, a liquid phase reaction is usually performed using a solvent as described below, but if the ligand used is liquid under the reaction conditions, it is also possible to use the ligand itself as the solvent and to adopt a reaction format in which no other solvent is added.

[0037] Furthermore, if a purification step and a redispersion step as described below are carried out before the ligand is coordinated, the desired ligand can be easily coordinated. In addition, when a non-coordinating solvent is used during the synthesis of semiconductor nanoparticles, the generation of defects on the surface of the semiconductor nanoparticles when the desired ligand is coordinated can be minimized, and a decrease in the fluorescence quantum efficiency can be prevented.

[0038] In one embodiment, the semiconductor nanoparticle-containing dispersion liquid after the production of the semiconductor nanoparticles is purified and redispersed, and then a solvent containing an aliphatic ligand is added, and a solvent containing a polar ligand is further added, and the mixture is stirred at 50° C. to 200° C. for 1 minute to 120 minutes in a nitrogen atmosphere to obtain the desired semiconductor nanoparticle composite. The aliphatic ligand and the polar ligand may be added simultaneously.

[0039] (purification) Semiconductor nanoparticles and semiconductor nanoparticle composites can be purified as follows. In one embodiment, the semiconductor nanoparticle composites can be precipitated from the dispersion by adding a polarity-reversing solvent such as acetone. The precipitated semiconductor nanoparticle composites can be collected by filtration or centrifugation, while the supernatant containing unreacted starting materials and other impurities can be discarded or reused. The precipitated semiconductor nanoparticle composites can then be washed with additional dispersion medium and dispersed again. This purification process can be repeated, for example, 2-4 times, or until the desired purity is reached. In the present invention, the method for purifying the semiconductor nanoparticle composite is not particularly limited, and in addition to the methods described above, for example, coagulation, liquid-liquid extraction, distillation, electrodeposition, size exclusion chromatography and / or ultrafiltration, or any other method can be used alone or in combination.

[0040] <Dispersion> In the present invention, the state in which the semiconductor nanoparticle composite is dispersed in a dispersion medium refers to a state in which the semiconductor nanoparticle composite does not precipitate or does not remain as visible turbidity (cloudiness) when the semiconductor nanoparticle composite is mixed with the dispersion medium. Note that the semiconductor nanoparticle composite dispersed in the dispersion medium is referred to as a semiconductor nanoparticle composite dispersion.

[0041] The semiconductor nanoparticle composite of the present invention can be dispersed in a dispersion medium to form a semiconductor nanoparticle composite dispersion liquid. It is preferable that the semiconductor nanoparticle composite can be dispersed in the dispersion medium to form a dispersion liquid even if the dispersion medium has an SP value of 9.0 or more. The SP value here is the Hildebrand solubility parameter, which is a value calculated from the Hansen solubility parameter, which can be determined using the values ​​in handbooks, such as “Hansen Solubility Parameters: A User's Handbook”, 2nd Edition, CM Hansen (2007), or the program in Practice (HSPiP) (2nd Edition) provided by Hanson and Abbot et al.

[0042] By setting the mass ratio of the aliphatic ligand to the polar ligand to the above ratio, the semiconductor nanoparticles can be dispersed in a dispersion medium having an SP value of 9.0 to 15.0. In particular, it is possible to disperse the semiconductor nanoparticles in at least one of acetone, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monomethyl ether (PGME), IPA, ethanol, methanol, and a mixture of any combination of these groups. By dispersing in these dispersion media, the semiconductor nanoparticle composite can be used while maintaining its dispersibility when applied to dispersion in a cured film or resin, which will be described later. In particular, in the field of photoresists, PGMEA is commonly used as a dilution solvent, and if the semiconductor nanoparticle composite is dispersible in PGMEA, the semiconductor nanoparticle composite can be widely applied to the photoresist field.

[0043] Furthermore, in the present invention, a monomer can be selected as a dispersion medium for dispersing the semiconductor nanoparticle composite. The monomer is not particularly limited, but is preferably an acrylic monomer, which allows a wide range of applications for the semiconductor nanoparticles. According to the application of the semiconductor nanoparticle composite dispersion, the (meth)acrylic monomer may be selected from methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, isoamyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, 3,5,5-trimethylcyclohexanol (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, methoxyethyl (meth)acrylate, ethyl carbitol (meth)acrylate, methoxytriethylene glycol acrylate, 2-ethylhexyl diglycol acrylate, methoxypolyethylene glycol acrylate, methoxyethyl (meth)acrylate, ethyl carbitol (meth)acrylate, methoxytriethylene glycol acrylate, 2-ethylhexyl diglycol acrylate, methoxypolyethylene glycol acrylate, methoxyethyl (meth) ... Dipropylene glycol acrylate, phenoxyethyl (meth)acrylate, 2-phenoxydiethylene glycol (meth)acrylate, 2-phenoxypolyethylene glycol (meth)acrylate (n≒2), tetrahydrofurfuryl (meth)acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, dicyclopentanyloxyl ether ethyl (meth)acrylate, isobornyloxylethyl (meth)acrylate, adamantyl (meth)acrylate, dimethyladamantyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, benzyl (meth)acrylate, ω-carboxy-polycaprolactone (n≒2) monoacrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-hydroxy-3-phenoxyethyl (meth)acrylate, (2-methyl-2-ethyl-1,The monomer may be selected from (meth)acrylic monomers such as 3-dioxolan-4-yl)methyl (meth)acrylate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, o-phenylphenol ethoxy (meth)acrylate, dimethylamino (meth)acrylate, diethylamino (meth)acrylate, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, glycidyl (meth)acrylate, 2-(meth)acryloyloxyethyl phosphate, acryloylmorpholine, dimethylacrylamide, dimethylaminopropylacrylamide, isopropylacrylamide, diethylacrylamide, hydroxyethylacrylamide, and N-acryloyloxyethylhexahydrophthalimide. These may be used alone or in combination of two or more. In particular, the acrylic monomer is preferably one or a mixture of two or more selected from lauryl (meth)acrylate and 1,6-hexadiol di(meth)acrylate depending on the application of the semiconductor nanoparticle composite dispersion liquid.

[0044] The semiconductor nanoparticle composite having the above-mentioned structure can be dispersed in a dispersion medium at a high mass fraction. The semiconductor nanoparticle composite is preferably dispersible in at least one of the dispersion medium and the monomer such that the mass fraction of the semiconductor nanoparticles is 25 mass% or more.

[0045] (Thermogravimetric analysis) Figure 1 shows the results of thermal analysis of a semiconductor nanoparticle composite according to an embodiment of the present invention. The thermal analysis is performed by thermogravimetry and ligand identification. The thermogravimetry was performed by using differential thermogravimetry-TG (DTA-TG) in a nitrogen atmosphere, heating the semiconductor nanoparticle composite at 10°C / min to 550°C, holding the temperature for 10 minutes, and then lowering the temperature. The solid line is the result of thermogravimetric analysis (TG), and the dashed line is the result of the derivative of TG (ΔTG). As the temperature of the semiconductor nanoparticle composite was increased, a mass loss due to the desorption of the ligand was observed. Since the mass loss was almost constant above 500°C (the mass loss rate per 10°C was less than 0.15%), most of the ligands in the semiconductor nanoparticle composite were desorbed by 500°C, and the proportion of the ligand amount in the entire semiconductor nanoparticles of this embodiment was calculated to be 32%. Furthermore, the mass loss rate (X H ) was 6% in the range of 350° C. or more and 550° C. or less. When the semiconductor nanoparticle composite was heated up to 700° C., almost all of the ligands were released from the semiconductor nanoparticles.

[0046] The semiconductor nanoparticle composite according to an embodiment of the present invention has a mass loss rate (X ) of the semiconductor nanoparticle composite in the range of 350° C. or more and 550° C. or less in thermogravimetric analysis relative to the mass fraction (L) of the total ligands in the semiconductor nanoparticle composite at room temperature. H ) percentage ({(X H ) / L}×100) is 10 or more and 55 or less. This means that, of all the ligands coordinated to the semiconductor nanoparticles at room temperature, 10 to 55 ligands in terms of mass ratio are released from the surface of the semiconductor nanoparticles not in the low temperature range from room temperature to 350°C, but in the high temperature range from 350°C to 550°C. When the ratio of ligands released from the surface of the semiconductor nanoparticles in the high temperature range from 350°C to 550°C is 10 to 55, this is an indicator that a semiconductor nanoparticle composite having high optical properties can be obtained. Note that the above ratio ({(X H ) / L}×100) is more preferably 10 to 50.

[0047] In addition, in a semiconductor nanoparticle composite according to another embodiment of the present invention, the mass loss rate of the semiconductor nanoparticle composite in the temperature range of 350° C. or more and 550° C. or less ((mass loss amount of semiconductor nanoparticle composite in the range of 350° C. to 550° C.) / (mass of semiconductor nanoparticle composite at room temperature)×100) is 2% or more and 15% or less. When the mass loss rate is within this range, the semiconductor nanoparticle composite has high fluorescence quantum efficiency.

[0048] In one embodiment of the present invention, the semiconductor nanoparticle composite has a mass loss ratio (X) of 1:1 when heated from room temperature to 700° C. to 1:1 when heated from room temperature to 350° C. L )" ratio (X L / X) and the "mass fraction of polar ligands in the semiconductor nanoparticle composite at room temperature (L)" relative to the "mass fraction of all ligands in the semiconductor nanoparticle composite at room temperature (L)" P The relationship between the ratio of (X L / X)<(L P / L). As above (X L / X)<(L P / L) is established, this means that at least a part of the polar ligands are strongly coordinated without being detached from the semiconductor nanoparticles even in a high temperature range of 350 ° C. or more. As described later, aliphatic ligands are detached from the surface of the semiconductor nanoparticles at a higher temperature range than polar ligands. The ligands strongly coordinated to the semiconductor nanoparticles in this way cover the surface of the semiconductor nanoparticles with a sufficient force to provide weather resistance to the surface of the semiconductor nanoparticles not only at room temperature but also in the temperature range used in applications, so that the semiconductor nanoparticle composite according to the embodiment of the present invention exhibits high optical activity. As described above, when the semiconductor nanoparticle composite of the present invention is heated to 700° C., almost all of the ligands are released from the semiconductor nanoparticles. Therefore, the "mass reduction rate (X) when the semiconductor nanoparticle composite is heated from room temperature to 700° C." and the "mass fraction (L) of all ligands coordinated to the semiconductor nanoparticles relative to the semiconductor nanoparticle composite at room temperature" are almost the same value.

[0049] Furthermore, from the above ΔTG results, two peaks were confirmed near 310°C and 430°C. These are due to the desorption of ligands. If the temperature at which the area of ​​each peak in the differential calorimetry exceeds 2% is taken as the desorption temperature of each ligand, the ligand desorption temperature at low temperature is calculated to be 205°C, and the ligand desorption temperature at high temperature is calculated to be 394°C. The desorbed ligands can be identified using infrared absorption spectroscopy.

[0050] First, the method for calculating the type and mass ratio of the ligand in the semiconductor nanoparticle composite using infrared absorption spectroscopy will be described. Infrared absorption spectrum data was collected for the semiconductor nanoparticle composite pellets prepared by the KBr pellet method using a JASCO FT / IR-4200. FIG. 2(a) shows the infrared absorption spectrum of the semiconductor nanoparticle composite of this embodiment. -1 , 1450cm -1 The CH stretching and CH bending absorption peaks are located near 1550 cm -1 The C=O stretching absorption peak is located near 1100 cm -1 The absorption peaks of CO stretching were observed around 2300 cm. -1 ~2500cm -1 The absorption peak that appears in is due to carbon dioxide.

[0051] 2(b), (c), and (d) show infrared absorption spectra of the ligand alone that is believed to be present in the semiconductor nanoparticle composite of this embodiment. In this embodiment, one polar ligand and two aliphatic ligands are coordinated to the semiconductor nanoparticle. In this embodiment, ligand (b) is a polar ligand, and ligands (c) and (d) are aliphatic ligands. Since the absorbance of an infrared absorption spectrum is proportional only to the concentration and thickness of a substance, quantitative analysis can be performed from the peak area.

[0052] In general, the infrared absorption spectrum of a semiconductor nanoparticle composite is expressed as SQD (ν), the infrared absorption spectrum of the i-th aliphatic ligand is S ai (ν), the infrared absorption spectrum of the i-th polar ligand is S pi (ν), it can be expressed as equation (1). S QD (ν) = ΣaiS ai (ν) + ΣpiS pi (ν) Equation (1) where ν is the wave number, and ai and pi are constants related to the mole fractions of aliphatic and polar ligands, respectively.

[0053] For example, the infrared absorption spectrum of the semiconductor nanoparticle composite of this embodiment is S (b) (ν), and the spectra of the aliphatic ligands in (c) and (d) are S (c) (ν), S (d) (ν), it can be expressed as equation (2). S QD (ν) = bS (b) (ν) + cS (c) (ν) + dS (d) (ν) Equation (2) Here, ν is the wave number, and b, c, and d are each constants. The values ​​of the constants b, c, and d that minimize the sum of squares of the residuals between the measured and calculated values ​​were determined using the solver function of Excel (a spreadsheet software made by Microsoft). Figure 3 shows the fitting of the measured and calculated values ​​of the infrared absorption spectrum. The dotted line shows the measured values, and the solid line shows the calculated values. It can be seen that the calculated values ​​closely represent the measured values.

[0054] FIG. 4 shows the composition of the infrared absorption spectrum of each ligand component in the fitting curve of the CH stretch absorption peak. In FIG. 4, as in FIG. 3 and FIG. 2, the dotted line shows the measured infrared absorption spectrum of the semiconductor nanoparticle composite, the gray solid line shows the measured infrared absorption spectrum of the ligand (b), and the two gray dashed lines show the measured infrared absorption spectrum of the ligands (c) and (d), respectively. The black solid line is the calculated value, and it can be seen that the calculated value well represents the measured value. Since the CH stretch absorption peak includes the absorption of all the ligand components in the semiconductor nanoparticle composite, the composition of the ligand can be obtained from the peak area ratio of each ligand component obtained by waveform separation. The mass fraction of each ligand component was calculated from the peak area ratio, the number of protons in the molecule, and the molecular weight. FIG. 4 shows the measurement results of the semiconductor nanoparticle composite obtained in Example 1 described later. In this example, the mass fraction of the ligand components was ligand (b):ligand (c):ligand (d)=89:8:3. In other words, the mass ratio of polar ligand (b) to aliphatic ligand ((c)+(d)) was calculated to be 89:11.

[0055] Using the methods described above, the ligands desorbed at low temperatures are identified in the thermal analysis. 5 shows infrared absorption spectra of the semiconductor nanoparticle composite of this embodiment before and after heat treatment. The solid line shows the infrared absorption spectrum of the semiconductor nanoparticle composite before heat treatment, and the dashed line shows the infrared absorption spectrum of the semiconductor nanoparticle composite heated to 350°C at 10°C / min in a nitrogen atmosphere and cooled to room temperature. In the infrared absorption spectrum of the semiconductor nanoparticle composite before heat treatment, -1 While a sharp absorption peak due to CO stretching is observed around 2900 cm, the intensity of this peak is considerably weaker in the semiconductor nanoparticle composite heated to 350 °C. -1 , 1450cm -1Since the CH stretching and CH bending absorption peaks are strongly observed around 2300 cm, the ligands that were desorbed at low temperatures confirmed by ΔTG are attributed to polar ligand (b), and the high-temperature desorption components above 350 °C are attributed to aliphatic ligands (c) and (d). -1 ~2500cm -1 The absorption peak that appears in is due to carbon dioxide.

[0056] The mass fraction (L) of all ligands in the semiconductor nanoparticle composite at room temperature is calculated as follows. In the above thermogravimetric analysis, the end point is the point where the mass loss of the semiconductor nanoparticle composite becomes almost constant, and the mass loss up to the end point indicates the total amount of ligands coordinated to the semiconductor nanoparticles at room temperature. The desorption temperature of the ligands varies depending on the type of ligands coordinated to the semiconductor nanoparticles. Therefore, in order to calculate the mass fraction (L) of the total ligands relative to the semiconductor nanoparticle composite at room temperature, it is sufficient to use the results of the thermogravimetric analysis (mass loss) when the heating temperature is 700°C or higher.

[0057] The above results of thermogravimetric analysis and infrared absorption spectroscopy indicate that when the semiconductor nanoparticle composite described in the present application is heated, the aliphatic ligands are desorbed from the surface of the semiconductor nanoparticles at a higher temperature than the polar ligands. Furthermore, at least a portion of the components that are desorbed at 350° C. or higher are attributed to the aliphatic ligands. For reference, Non-Patent Document 6 discloses that the aliphatic ligand (dodecanethiol) is released from the bound Zn at about 250° C. to 300° C. The release temperature of the aliphatic ligand in the semiconductor nanoparticle composite described in the present application is higher than that in the literature. The desorption temperature of the ligand is considered to be greatly influenced not only by the chemical structure but also by the interaction with surrounding atoms and molecules, such as the coordination form with Zn present on the surface of the semiconductor nanoparticles and the formation of the ligand's crystal structure. The aliphatic ligands coordinated to the semiconductor nanoparticles described in the present application are strongly bound to the surface of the semiconductor nanoparticles due to the factors described above, and exhibit a high desorption temperature. The inventors speculate that the presence of the aliphatic ligands strongly bound to the surface of the semiconductor nanoparticles in this way improves the fluorescence quantum efficiency of the semiconductor nanoparticles. The inventors speculate that the presence of the aliphatic ligands described above also has the effect of improving heat resistance.

[0058] The semiconductor nanoparticle composite of the present invention has the following configuration. (1) A semiconductor nanoparticle composite in which two or more types of ligands, including an aliphatic ligand and a polar ligand, are coordinated to the surface of a semiconductor nanoparticle, The ligand comprises an organic group and a coordinating group, The aliphatic ligand has an aliphatic hydrocarbon group as the organic group. The polar ligand comprises a hydrophilic functional group on the organic group, the mass ratio of the aliphatic ligand to the polar ligand (aliphatic ligand / polar ligand) is 0.05 to 1.00; The mass loss rate (X) of the semiconductor nanoparticle composite at room temperature in the range of 350°C to 550°C in thermogravimetric analysis is H ) percentage ({(X H ) / L}×100) is 10 or more and 55 or less, Semiconductor nanoparticle composites. (2) A semiconductor nanoparticle composite in which two or more types of ligands, including an aliphatic ligand and a polar ligand, are coordinated to the surface of a semiconductor nanoparticle, The ligand comprises an organic group and a coordinating group, The aliphatic ligand has an aliphatic hydrocarbon group as the organic group. The polar ligand comprises a hydrophilic functional group on the organic group, the mass ratio of the aliphatic ligand to the polar ligand (aliphatic ligand / polar ligand) is 0.05 to 1.00; The mass loss rate (X H ) is 2% or more and 15% or less, Semiconductor nanoparticle composites. (3) when the semiconductor nanoparticle composite is heated, the polar ligands are desorbed from the surface of the semiconductor nanoparticles at a lower temperature than the aliphatic ligands; The semiconductor nanoparticle composite according to (1) or (2) above. (4) In the thermogravimetric analysis, The mass loss rate (X) when the semiconductor nanoparticle composite is heated from room temperature to 700°C is compared with the mass loss rate (X) in the range from room temperature to 350°C. L ) ratio (X L / X) and The mass fraction of polar ligands in the semiconductor nanoparticle composite at room temperature (L) relative to the mass fraction of all ligands in the semiconductor nanoparticle composite at room temperature (L P ) ratio (L P / L) and the relationship is (X L / X)<(L P / L) The semiconductor nanoparticle composite according to any one of (1) to (3) above. (5) The semiconductor nanoparticle composite is dispersible in a dispersion medium having an SP value of 9.0 to 15.0. The semiconductor nanoparticle composite according to any one of (1) to (4) above. (6) The dispersion medium is one or more mixed dispersion media selected from the group consisting of acetone, PGMEA, PGME, IPA, ethanol, and methanol; The semiconductor nanoparticle composite according to (5) above. (7) At least a portion of the mass loss at 350° C. or higher is attributable to elimination of the aliphatic ligand; The semiconductor nanoparticle composite according to any one of (1) to (6) above. (8) The aliphatic ligand has one coordinating group and at least one aliphatic hydrocarbon group bonded thereto. The semiconductor nanoparticle composite according to any one of (1) to (7) above. (9) The molecular weight of the polar ligand is 50 or more and 600 or less. The semiconductor nanoparticle composite according to any one of (1) to (8) above. (10) The molecular weight of the polar ligand is 50 or more and 450 or less. The semiconductor nanoparticle composite according to any one of (1) to (9) above. (11) The coordinating group of the aliphatic ligand is selected from the group consisting of an amino group, a carboxyl group, a mercapto group, a phosphine group, and a phosphine oxide group; The semiconductor nanoparticle composite according to any one of (1) to (10) above. (12) The organic group of the polar ligand has at least one of a hydroxyl group, a carboxyl group, a carbonyl group, a mercapto group, an amino group, an ether bond, an ester bond, and a siloxane bond. The semiconductor nanoparticle composite according to any one of (1) to (11) above. (13) The coordinating group of the polar ligand is a mercapto group. The semiconductor nanoparticle composite according to any one of (1) to (12) above. (14) A mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is 0.1 to 0.7. The semiconductor nanoparticle composite according to any one of (1) to (13) above. (15) A mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) is 0.1 to 0.5. The semiconductor nanoparticle composite according to any one of (1) to (14) above. (16) The semiconductor nanoparticles can be dispersed in the dispersion medium so that the mass fraction of the semiconductor nanoparticles is 25 mass% or more. The semiconductor nanoparticle composite according to any one of (5) to (15) above. (17) The semiconductor nanoparticles can be dispersed in the dispersion medium so that the mass fraction of the semiconductor nanoparticles is 35 mass% or more. The semiconductor nanoparticle composite according to any one of (5) to (16) above. (18) The semiconductor nanoparticles contain Zn on the surface of the semiconductor nanoparticles. The semiconductor nanoparticle composite according to any one of (1) to (17) above. (19) The semiconductor nanoparticle composite has a fluorescence quantum efficiency of 80% or more. The semiconductor nanoparticle composite according to any one of (1) to (18) above. (20) The half width of the emission spectrum of the semiconductor nanoparticle composite is 40 nm or less. The semiconductor nanoparticle composite according to any one of (1) to (19) above. (21) The semiconductor nanoparticles contain In and P. The semiconductor nanoparticle composite according to any one of (1) to (20) above.

[0059] (The Doctrine of Equivalents) It will be understood that the structures and / or methods described herein are presented as examples, and that numerous variations are possible, and that these specific examples or examples should not be taken in a limiting sense. A particular procedure or method described herein may represent one of many process methods. Thus, various acts illustrated and / or described may be performed in the order illustrated and / or described, or may be omitted. Similarly, the order of the methods described above may be altered. The subject matter of the present disclosure includes all novel and non-obvious combinations and subcombinations of the various methods, systems, and structures, as well as other features, functions, acts, and / or properties disclosed herein, and all equivalents thereof. EXAMPLES

[0060] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these.

[0061] [Example 1] First, semiconductor nanoparticles were synthesized according to the following method. (Preparation of precursors) (Preparation of Zn precursor solution) 40 mmol of zinc oleate and 75 mL of octadecene were mixed and heated at 110 °C for 1 hour under vacuum to prepare a Zn precursor with [Zn] = 0.4 M. (Preparation of Se precursor (trioctylphosphine selenide)) 22 mmol of selenium powder and 10 mL of trioctylphosphine were mixed in nitrogen and stirred until completely dissolved to obtain trioctylphosphine selenide with [Se] = 2.2 M. (Preparation of S precursor (trioctylphosphine sulfide)) 22 mmol of sulfur powder and 10 mL of trioctylphosphine were mixed in nitrogen and stirred until completely dissolved to obtain trioctylphosphine sulfide with [S] = 2.2 M.

[0062] (Synthesis of semiconductor nanoparticles) Indium acetate (0.3 mmol) and zinc oleate (0.6 mmol) were added to a mixture of oleic acid (0.9 mmol), 1-dodecanethiol (0.1 mmol), and octadecene (10 mL), heated to about 120 °C under vacuum (<20 Pa), and reacted for 1 hour. The mixture reacted under vacuum was brought to 25 °C under a nitrogen atmosphere, and after adding tris(trimethylsilyl)phosphine (0.2 mmol), it was heated to about 300 °C and reacted for 10 minutes. The reaction solution was cooled to 25 °C, octanoyl chloride (0.45 mmol) was injected, heated at about 250 °C for 30 minutes, and then cooled to 25 °C. Thereafter, it was heated to 200 °C, 0.75 mL of the Zn precursor solution and 0.3 mmol of trioctylphosphine selenide were simultaneously added and reacted for 30 minutes to form a ZnSe shell on the surface of the InP-based semiconductor nanoparticles. Further, 1.5 mL of the Zn precursor solution and 0.6 mmol of trioctylphosphine sulfide were added, the temperature was raised to 250 °C and reacted for 1 hour to form a ZnS shell. The reaction solution of the semiconductor nanoparticles obtained by synthesis as described above was added to acetone, mixed well, and then centrifuged. The centrifugal acceleration was set to 4000G. The precipitate was collected, and normal hexane was added to the precipitate to prepare a dispersion. This operation was repeated several times to obtain purified semiconductor nanoparticles.

[0063] Subsequently, the synthesis of the semiconductor nanoparticle composite was carried out according to the following method. (Preparation of Ligand Monomer) (Preparation of PEG-SH) A flask was charged with 210 g of methoxy PEG-OH (molecular weight 400) and 93 g of triethylamine, and dissolved in 420 mL of THF (tetrahydrofuran). The solution was cooled to 0 °C, and 51 g of methanesulfonyl chloride was gradually added dropwise under a nitrogen atmosphere while taking care that the temperature of the reaction solution did not exceed 5 °C due to the heat of reaction. Thereafter, the reaction solution was warmed to room temperature and stirred for 2 hours. This solution was extracted with a chloroform-water system, and the organic phase was recovered. The obtained solution was concentrated by evaporation to obtain an oily intermediate with magnesium sulfate. This was transferred to another 1 L flask, and 400 mL of 1.3 M aqueous thiourea solution was added under a nitrogen atmosphere. After the solution was refluxed for 2 hours, 21 g of NaOH was added, and reflux was continued for another 1.5 hours. The reaction solution was cooled to room temperature, and 1 M aqueous HCl solution was added until pH = 7 to neutralize it. The obtained solution was extracted with a chloroform-water system to obtain the target ligand (PEG-SH, molecular weight 430). In the step of synthesizing PEG-SH with a molecular weight of 400, PEG-SH with a molecular weight of 600 was obtained in the same manner except that methoxy PEG-OH (molecular weight 400, 210 g) was changed to methoxy PEG-OH (molecular weight 600, 315 g). (Preparation of N-acetyl-N-(2-mercaptoethyl)propanamide) 1.2g (10mmol) of N-(2-sulfanylethyl)acetamide and 1.7mL (12mmol) of triethylamine were placed in a 100mL round-bottom flask and dissolved in 30mL of dehydrated dichloromethane. The solution was cooled to 0℃, and 0.87mL (10mmol) of propanoyl chloride was slowly added dropwise under a nitrogen atmosphere, taking care not to raise the temperature of the solution above 5℃. After the addition was completed, the reaction solution was warmed to room temperature and stirred for 2 hours. The reaction solution was filtered, and the filtrate was diluted with chloroform. The solution was extracted in the order of 10% HCl aqueous solution, 10% Na2CO3 aqueous solution, and saturated NaCl aqueous solution, and the organic phase was recovered. The organic phase was concentrated by evaporation, and then purified by column chromatography using a hexane-ethyl acetate mixed solvent as the developing solvent to obtain the target product.

[0064] (Preparation of semiconductor nanoparticle composites) A semiconductor nanoparticle 1-octadecene dispersion was prepared by dispersing the purified semiconductor nanoparticles in 1-octadecene in a flask to a mass ratio of 10%. 10.0 g of the prepared semiconductor nanoparticle 1-octadecene dispersion was placed in a flask, 0.2 g of dodecanethiol (DDT) was added as an aliphatic ligand, and 4.0 g of PEG-SH was added as a polar ligand. The mixture was stirred at 110°C for 60 minutes under a nitrogen atmosphere and cooled to 25°C to obtain a semiconductor nanoparticle composite. The reaction solution containing the semiconductor nanoparticle composite was transferred to a centrifuge tube and centrifuged at 4000G for 20 minutes, resulting in separation into a transparent 1-octadecene phase and a semiconductor nanoparticle composite phase. The 1-octadecene phase was removed, and the remaining semiconductor nanoparticle composite phase was collected.

[0065] (Cleaning process) 5.0 mL of acetone was added to the obtained semiconductor nanoparticle composite phase to prepare a dispersion. 50 mL of normal hexane was added to the obtained dispersion, and the mixture was centrifuged at 4000 G for 20 minutes. After centrifugation, the transparent supernatant was removed and the precipitate was collected. This operation was repeated several times to obtain a purified semiconductor nanoparticle composite. (Measurement of the luminescence properties of semiconductor nanoparticle composites) The luminescence properties of the semiconductor nanoparticle composite were measured using a fluorescence quantum efficiency measurement system (QE-2100, manufactured by Otsuka Electronics). The obtained semiconductor nanoparticle composite was dispersed in a dispersion medium and exposed to a single light of 450 nm to obtain an emission spectrum. The fluorescence quantum efficiency (QY) and full width at half maximum (FWHM) were calculated from the emission spectrum after re-excitation correction, which was obtained by removing the re-excitation fluorescence emission spectrum of the fluorescent light emitted by re-excitation from the obtained emission spectrum. PGMEA was used as the dispersion liquid. When not dispersing in PGMEA, the dispersion liquid was changed to normal hexane.

[0066] (Thermogravimetric analysis of semiconductor nanoparticle composites) 1 shows the TG curve and its derivative (ΔTG) curve when the semiconductor nanoparticle composite (Example 1) having the above-mentioned configuration was heated from 25° C. to 550° C. at 10° C. / min by thermogravimetric analysis (TGA). The measurement was performed using a Bruker TG-DTA2000SA under a nitrogen flow of 200 ml / min. In the semiconductor nanoparticle composite of Example 1, the mass loss rate was 25% in the range of room temperature to 350° C., and the mass loss rate of the semiconductor nanoparticle composite was 7% in the range of 350° C. to 550° C. Furthermore, two peaks were confirmed near 310° C. and 430° C. from the ΔTG curve.

[0067] In the present invention, the total mass loss rate when the semiconductor nanoparticle composite was heated to 700° C. in thermogravimetric analysis was regarded as the mass fraction (L) of all ligands relative to the semiconductor nanoparticle composite at room temperature. Furthermore, in a thermogravimetric analysis, the semiconductor nanoparticle composite was heated to 700°C, and the residual mass after measurement was taken as the mass of the semiconductor nanoparticles. From this value, the mass fraction (Q) of the semiconductor nanoparticles relative to the semiconductor nanoparticle composite at room temperature was confirmed. With reference to the mass fraction (Q) of the semiconductor nanoparticles relative to the semiconductor nanoparticle composite at room temperature, PGMEA (SP value 9.41) was added to the semiconductor nanoparticle composite so that the mass fraction of the semiconductor nanoparticles was 5% by mass, and the dispersion state at that time was confirmed. Table 2 shows that the semiconductor nanoparticles were dispersed and shows that precipitation and turbidity were observed. The amount of PGMEA added was adjusted so that the mass fraction of the semiconductor nanoparticles changed in 5% by mass increments from 50% by mass to 10% by mass, and the dispersion state was confirmed. The mass fraction at which precipitation and turbidity were no longer observed was shown in Table 2 as the mass fraction of the semiconductor nanoparticles. The following Examples 2 to 21 were also measured in the same manner, and the results are shown in Table 2.

[0068] [Example 2] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand and 4.0 g of PEG-SH was used as the polar ligand.

[0069] [Example 3] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, 1.0 g of dodecanethiol was used as the aliphatic thiol ligand, 1.5 g of N-acetyl-N-(2-mercaptoethyl)propanamide was used as the polar ligand, and 0.5 g of oleic acid was further added.

[0070] [Example 4] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand, 4.0 g of triethylene glycol monomethyl ether thiol (TEG-SH) was used as the polar ligand, and 0.5 g of oleic acid was further added.

[0071] [Example 5] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of preparing the semiconductor nanoparticle composite, 0.5 g of octanethiol was used as the aliphatic thiol ligand and 4.0 g of N-acetyl-N-(2-mercaptoethyl)propanamide was used as the polar ligand.

[0072] [Example 6] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand and 6.0 g of PEG-SH (molecular weight 600) was used as the polar ligand.

[0073] [Example 7] In the step of preparing the shell of the semiconductor nanoparticles, a mixture of 40 mmol of zinc octanoate and 75 mL of octadecene was used as the Zn precursor solution. Furthermore, in the step of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand, 4.0 g of N-acetyl-N-(2-mercaptoethyl)propanamide was used as the polar ligand, and 0.5 g of caprylic acid (octanoic acid) was added. A semiconductor nanoparticle composite was obtained in the same manner as in Example 1.

[0074] [Example 8] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand and 4.0 g of methyl 3-mercaptopropionate (manufactured by Tokyo Chemical Industry Co., Ltd.) was used as the polar ligand.

[0075] [Example 9] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of preparing the semiconductor nanoparticle composite, 0.2 g of dodecanethiol was used as the aliphatic thiol ligand and 8.0 g of PEG-SH was used as the polar ligand.

[0076] [Example 10] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, 0.5 g of cyclopentanethiol was used as the aliphatic thiol ligand, 4.0 g of PEG-SH was used as the polar ligand, and 0.5 g of oleic acid was further added.

[0077] FIG. 6 is a graph showing the results of thermal analysis of the semiconductor nanoparticle composite of Example 10. The solid line is the TG curve, and the dashed line is the ΔTG curve. In Example 10, cyclopentanethiol is used as the aliphatic ligand, and PEG-SH is used as the polar ligand. In the ΔTG curve of Example 10, a peak due to the elimination of cyclopentanethiol was observed near 230° C., and a peak due to PEG-SH was observed near 310° C. In this way, when the aliphatic ligand is eliminated faster than the polar ligand, the fluorescence quantum efficiency of the semiconductor nanoparticles is reduced.

[0078] [Example 11] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, 0.5 g of pentanethiol was used as the aliphatic thiol ligand, 4.0 g of PEG-SH was used as the polar ligand, and 0.5 g of oleic acid was further added.

[0079] [Example 12] In the step of preparing the shell of the semiconductor nanoparticles, a mixture of 40 mmol of zinc acetate and 75 mL of octadecene was used as the Zn precursor solution. Furthermore, in the step of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand, 4.0 g of PEG-SH was used as the polar ligand, and 0.5 g of acetic acid was added. A semiconductor nanoparticle composite was obtained in the same manner as in Example 1.

[0080] [Example 13] In the process of preparing the semiconductor nanoparticle composite, 2.0 g of dodecanethiol was added as the aliphatic thiol ligand, the polar ligand was changed to PEG-SH, and 1.0 g of oleic acid was added. The mixture was stirred for 60 minutes at 110°C under a nitrogen atmosphere and cooled to 25°C. 5.0 mL of normal hexane was added to the reaction solution to prepare a dispersion. 50 mL of ethanol was added to the obtained dispersion, and the mixture was centrifuged at 4000G for 20 minutes. After centrifugation, the transparent supernatant was removed and the precipitate was collected. This operation was repeated several times to obtain a purified semiconductor nanoparticle composite.

[0081] [Example 14] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand and 7.5 g of PEG-SH (molecular weight 750) was used as the polar ligand.

[0082] [Example 15] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand and 10.0 g of PEG-SH (molecular weight 1000) was used as the polar ligand.

[0083] [Example 16] In a flask, 1.0 g of the semiconductor nanoparticle composite purified in the same manner as in Example 1, 10 mL of isopropanol, and 4.0 g of PEG-SH were placed. The solution was stirred at 80°C for 180 minutes under a nitrogen atmosphere and cooled to 25°C. 50 mL of normal hexane was added to the reaction solution, and the mixture was centrifuged at 4000G for 20 minutes. After centrifugation, the transparent supernatant was removed and the precipitate was collected. 5.0 mL of acetone was added to the precipitate to prepare a dispersion. 50 mL of normal hexane was added to the obtained dispersion, and the mixture was centrifuged at 4000G for 20 minutes. After centrifugation, the transparent supernatant was removed and the precipitate was collected. This operation was repeated several times to obtain a purified semiconductor nanoparticle composite.

[0084] FIG. 7 is a graph showing the results of thermal analysis of the semiconductor nanoparticle composite of Example 16. The solid line is the TG curve, and the dashed line is the ΔTG curve. In the ΔTG curve of the semiconductor nanoparticle composite of Example 16, a sharp single peak was observed near 300°C. When the type of ligand causing the peak was identified using infrared absorption spectroscopy, it was found that the peak was caused by a polar ligand (PEG-SH). On the other hand, when the ligand that was detached in the range of 350°C to 550°C was also identified using infrared absorption spectroscopy, it was found that the ligand that was detached in the range of 350°C to 550°C was caused by an aliphatic ligand. Focusing on the mass loss rate by thermal analysis, the mass loss rate in the range of 350°C to 550°C was 1%. Thus, when the mass loss rate in the range of 350°C to 550°C is less than 2%, the fluorescence quantum efficiency of the semiconductor nanoparticle composite is low.

[0085] [Example 17] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand, 2.0 g of PEG-SH was used as the polar ligand, and 2.0 g of oleic acid was further added.

[0086] FIG. 8 is a graph showing the results of thermal analysis of the semiconductor nanoparticle composite of Example 17. The solid line is the TG curve, and the dashed line is the ΔTG curve. Dodecanethiol and oleic acid are used as the aliphatic ligands, and PEG-SH is used as the polar ligand. In the ΔTG curve of Example 17, a peak due to the detachment of the polar ligand was observed near 310° C., and a peak due to the detachment of the aliphatic ligand was observed near 440° C. In addition, focusing on the mass reduction rate by thermal analysis, the mass reduction rate in the range of 350° C. to 550° C. was 17%. Thus, when the mass reduction rate in the range of 350° C. to 550° C. is 15% or more, the fluorescence quantum efficiency of the semiconductor nanoparticle composite is low.

[0087] [Example 18] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the process of preparing the semiconductor nanoparticle composite, 0.5 g of dodecanethiol was used as the aliphatic thiol ligand, 2.0 g of N-acetyl-N-(2-mercaptoethyl)propanamide was used as the polar ligand, and 2.0 g of oleic acid was further added.

[0088] [Example 19] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of producing the semiconductor nanoparticle composite, 4.0 g of dodecanethiol was used as the aliphatic thiol ligand and no polar ligand was added.

[0089] [Example 20] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of preparing the semiconductor nanoparticle composite, no aliphatic thiol ligand and no polar ligand were added, and 4.0 g of oleic acid was added.

[0090] [Example 21] A semiconductor nanoparticle composite was obtained in the same manner as in Example 1, except that in the step of preparing the semiconductor nanoparticle composite, no aliphatic thiol ligand was added and 4.0 g of PEG-SH was used as the polar ligand.

[0091] The ligand configuration of the obtained semiconductor nanoparticle composite is shown in Table 1, and the luminescence characteristics, the results of thermal analysis, and the dispersion state in the dispersion medium are shown in Table 2. The semiconductor nanoparticle composite is preferably one that can be dispersed in PGMEA such that the mass fraction of the semiconductor nanoparticles is 25 mass% or more. The meanings of the abbreviations shown in Table 1 are as follows: DDT: Dodecanethiol Oct-SH: Octanethiol OA: Oleic acid OctA: Octanoic acid

[0092] [Table 1]

[0093]

Table 2

Claims

1. A semiconductor nanoparticle composite in which two or more types of ligands, including an aliphatic ligand and a polar ligand, are coordinated to the surface of a semiconductor nanoparticle, The ligand comprises an organic group and one coordinating group; The aliphatic ligand has an aliphatic hydrocarbon group as the organic group and a carboxy group or a mercapto group as the coordinating group, The polar ligand includes at least one of a carbonyl group, an ether bond, and an ester bond in the organic group, and the coordinating group is a mercapto group; The molecular weight of the polar ligand is 50 or more and 600 or less, the mass ratio of the aliphatic ligand to the polar ligand (aliphatic ligand / polar ligand) is 0.05 to 1.00; a mass ratio of the aliphatic ligand and the polar ligand to the semiconductor nanoparticles ((aliphatic ligand and polar ligand) / semiconductor nanoparticles) of 0.1 to 0.7; The mass fraction (L) of the semiconductor nanoparticle composite at room temperature is expressed as the mass loss rate (X H ) ratio ({(X H ) / L}×100) is 10 or more and 55 or less, Semiconductor nanoparticle composites.

2. A semiconductor nanoparticle composite in which two or more types of ligands, including an aliphatic ligand and a polar ligand, are coordinated to the surface of a semiconductor nanoparticle, The ligand comprises an organic group and one coordinating group; The aliphatic ligand has an aliphatic hydrocarbon group as the organic group and a carboxy group or a mercapto group as the coordinating group, The polar ligand includes at least one of a carbonyl group, an ether bond, and an ester bond in the organic group, and the coordinating group is a mercapto group; The molecular weight of the polar ligand is 50 or more and 600 or less, the mass ratio of the aliphatic ligand to the polar ligand (aliphatic ligand / polar ligand) is 0.05 to 1.00; a mass ratio of the aliphatic ligand and the polar ligand to the semiconductor nanoparticles ((aliphatic ligand and polar ligand) / semiconductor nanoparticles) of 0.1 to 0.7; The mass loss rate (X H ) is 2% or more and 15% or less, Semiconductor nanoparticle composites.

3. When the semiconductor nanoparticle composite is heated, the polar ligands are desorbed from the surface of the semiconductor nanoparticles at a lower temperature than the aliphatic ligands. The semiconductor nanoparticle composite according to claim 1 or 2.

4. In the thermogravimetric analysis, The mass loss rate (X) when the semiconductor nanoparticle composite is heated from room temperature to 700° C. is compared with the mass loss rate (X) in the range from room temperature to 350° C. L ) ratio (X L / X) and The mass fraction of polar ligands in the semiconductor nanoparticle composite at room temperature (L) relative to the mass fraction of all ligands in the semiconductor nanoparticle composite at room temperature (L P ) ratio (L P / L) and the relationship is (X L / X) < (L P / L), The semiconductor nanoparticle composite according to any one of claims 1 to 3.

5. The semiconductor nanoparticle composite is dispersible in a dispersion medium having an SP value of 9.0 to 15.

0. The semiconductor nanoparticle composite according to any one of claims 1 to 4.

6. The dispersion medium is one or more mixed dispersion media selected from the group consisting of acetone, PGMEA, PGME, IPA, ethanol, and methanol; The semiconductor nanoparticle composite of claim 5 .

7. At least a portion of the mass loss at 350° C. or higher is attributable to elimination of the aliphatic ligands. The semiconductor nanoparticle composite according to any one of claims 1 to 6.

8. The aliphatic ligand has one coordinating group and at least one aliphatic hydrocarbon group bonded thereto. The semiconductor nanoparticle composite according to any one of claims 1 to 7.

9. a mass ratio of the ligand to the semiconductor nanoparticles (ligand / semiconductor nanoparticles) of 0.1 to 0.7; The semiconductor nanoparticle composite according to any one of claims 1 to 8.

10. The semiconductor nanoparticles can be dispersed in the dispersion medium so that the mass fraction of the semiconductor nanoparticles is 25 mass% or more. The semiconductor nanoparticle composite according to any one of claims 5 to 9.

11. The semiconductor nanoparticles contain Zn on the surface of the semiconductor nanoparticles. The semiconductor nanoparticle composite according to any one of claims 1 to 10.

12. The semiconductor nanoparticle composite has a fluorescence quantum efficiency of 80% or more. The semiconductor nanoparticle composite according to any one of claims 1 to 11.

13. The half width of the emission spectrum of the semiconductor nanoparticle composite is 40 nm or less. The semiconductor nanoparticle composite according to any one of claims 1 to 12.

14. The semiconductor nanoparticles include In and P; The semiconductor nanoparticle composite according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Titanium compound containing quantum dots and production method, and photoelectric conversion element using the titanium compound containing quantum dots

    JP2013136498A

  • Reactive colloidal nanocrystals and nanocrystal composites

    JP2017533875A

  • Luminous body, light emitting film, light emitting diode, and light emitting device having luminous body

    JP2019073705A

  • Quantum dots and method for producing same, and molded body, sheet member, wavelength conversion member and light-emitting device which use quantum dots

    WO2015156226A1

  • Semiconductor nanoparticles, dispersion liquid, film, and method for producing semiconductor nanoparticles

    WO2017038487A1